Uniform and local degradation of epoxy-based powder coatings: Salt transport and accelerated exposure analysis - Hossein Zargarnezhad; Dennis Wong; C.N. Catherine Lam; Edouard Asselin (Journal of Pipeline Science and Engineering)
The barrier performance of epoxy-based powder coatings for pipelines was evaluated through salt transport measurements through free-standing coating films and via cyclic testing of coated steel panels. The permeability of salt through the free-standing coating films was measured using reverse osmosis techniques under hydraulic pressures relevant to industrial use. These tests showed that fusion bonded epoxy (FBE) and high-performance powder coating (HPPC) have low salt permeability. Accelerated exposure tests were then conducted on the coated steel panels, subjecting them to humidified environments, ultraviolet (UV) light, and salt/fog conditions, all in accordance with ASTM D5894. Some of the exposure conditions (e.g., intensity of UV light and humidity) were modified to examine the impact of each parameter on the relative performance of these coating systems. The reversibility of the coating properties was characterized by a thermal cycling protocol and adhesion performance analysis. Alternative exposure to dry- and wet-cycles (at 60 °C and 50 °C, respectively), salt/fog conditions and UV light results in irreversible damage to the coatings as early as two weeks. However, coated panels exposed to a lower UV intensity (one tenth of the value defined by the standard) showed minimal degradation of FBE, meaning that the most critical parameter was the UV radiation exposure. For one 336-h ageing sequence under UV exposure, the HPPC exhibited superior performance compared to FBE. More importantly, our extended exposure sequences showed that while the FBE coating structure undergoes a slow ablation process, indicating significant surface damage, it still retains its effectiveness as a barrier. However, the osmotic pressures around coated pipes and the pre-existing, unavoidable porosity throughout the coating thickness can facilitate local through-thickness pinholes, which could potentially serve as areas susceptible to cathodic disbondment.